The Relationship between Age and Education with Elderly Persons Activeness Participating in Posbindu Activities in the Working Area of Puskesmas Pagar Agung Lahat in 2022 - Lusiana; Abdul Somad; Detiana (Formosa Journal of Science and Technology, 2023)
The high number of PTM problems in Indonesia requires adequate and comprehensive control through health promotion, early detection, and appropriate and accurate information. This study uses the Correlation Study research method, which is research that aims to reveal the correlation relationship between the independent variables and the dependent variable. The results of statistical tests with Fisher's exact obtained p value = 0.02% (p <α = 0.05). This shows that there is a significant relationship between age and the activity of the elderly in participating in Posbindu activities. Test results with Fisher's exact results obtained p value = 0.02% (p <α = 0.05). This shows that there is a significant relationship between education and the activeness of the elderly in participating in Posbindu activities.